1986
DOI: 10.2466/pms.1986.63.1.215
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Voice Fundamental Frequency in Elderly Female Speakers

Abstract: Three groups of women, of mean age 21, 72, and 84 yr. (ns = 34, 17, 17), were tape-recorded while describing the "Cookie Thief" picture of the Boston Diagnostic Aphasia Test. Voice fundamental frequency (fo) was measured for a 30-sec. sample from the middle of their descriptions. Analysis showed that the two elderly groups' mean fo was significantly lower than the younger females', but no differences between means were significant for the older groups. Similar findings were obtained for variability of performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
3
8
0
3
Order By: Relevance
“…Consistent with a large number of previous reports [3,4,[7][8][9][10][11][12][13][14][15][16] , our results showed that SFF in females decreases in association with aging. However, the range of decrease in SFF was larger than conventionally reported.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Consistent with a large number of previous reports [3,4,[7][8][9][10][11][12][13][14][15][16] , our results showed that SFF in females decreases in association with aging. However, the range of decrease in SFF was larger than conventionally reported.…”
Section: Discussionsupporting
confidence: 82%
“…The results of previous studies are highly consistent in that SFF decreased with advancing age [3,4,[7][8][9][10][11][12][13][14][15][16] . However, considerable differences are seen in the degree of change in SFF associated with aging among investigators.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Benja min [22] observe une augmentation de la variation de la fréquence fondamentale avec l'âge chez les hommes et les femmes, tandis que Morgan et Rastatter [23] constatent l'in verse chez des femmes âgées par rapport à des femmes plus jeunes. Par ailleurs, on sait que la fréquence fondamentale à la tin d'une phrase interrogative est plus élevée que celle de la fin d'une phrase déclarative [24] surtout s'il s'agit d'interrogatives non marquées gram maticalement [25].…”
Section: Normalwerte Gewisser Elemente Der Prosodie Bei Französischspunclassified